981. Extended Adherence and Persistence to HIV PrEP in a Multidisciplinary PrEP Clinic. (31st December 2020) - Whelchel, Kristen; Zuckerman, Autumn; DeClercq, Josh; Choi, Leena; Rashid, Shahristan; Kelly, Sean
Abstract: Background: Methods to identify and address barriers to human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) persistence are needed to improve low PrEP persistence rates beyond 6 months. We evaluated PrEP adherence and persistence in a multidisciplinary clinic model with an integrated specialty pharmacist. Methods: We conducted a single-center, retrospective, cohort study of patients initiating PrEP in the multidisciplinary Vanderbilt PrEP Clinic with prescriptions filled by Vanderbilt Specialty Pharmacy between 9/1/2016 and 3/31/2019. In this model, integrated clinical pharmacists manage PrEP access, affordability, and therapy monitoring. Clinical data were collected from the electronic health records and pharmacy claims data. Adherence was calculated from fill data using proportion of days covered (PDC). Persistence at 6, 12 and 18 months was measured using patient-reported discontinuation date or the date of the last fill plus the fill's days' supply for patients lost to follow-up. The Kaplan-Meier estimation method was used to estimate persistence probabilities. Results: Most of the 63 patients included were male (97%), white (84%), commercially insured (94%) with a median age of 38 years, and men who have sex with men at high risk for acquiring HIV (97%); Table 1. The majority of patients with at least one follow-up visit (n=58) reported no adverse effects (78%), no missed doses (71%), and had a median PDC of 99% (IQR 97% – 100%). Persistence at 6, 12 and 18 months was 0.87 (95% confidence interval, CI, 0.80 – 0.96), 0.81 (95% CI 0.72 – 0.91), and 0.74 (95% CI 0.64 – 0.86), respectively; Figure 1. Of the 18 patients who discontinued PrEP, 9 discontinued due to perceived lack of risk for acquiring HIV, 6 were lost to follow up, 1 moved, transferring PrEP care to a new provider, 1 had worsening depression, and 1 had renal function decline. Table 1 Patient Characteristics Figure 1 Persistence on HIV PrEP Conclusion: Patients receiving PrEP treatment in a multidisciplinary clinic with an integrated clinical pharmacist had high rates of adherence and persistence up to 18 months. Patients reported few side effects and reasons for therapy discontinuation were appropriate. Efforts to incorporate pharmacy support in managing PrEP patients could be beneficial in increasing patient adherence and persistence. Disclosures: All Authors : No reported disclosures